Social informatics : 11th International Conference, SocInfo 2019, Doha, Qatar, November 18-21, 2019, Proceedings /: 11th International Conference, SocInfo 2019, Doha, Qatar, November 18-21, 2019, Proceedings. (2019) - Unknown
No abstract available